2024
DOI: 10.3390/jof10030182
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Effectiveness of Biochar Coupled with Arbuscular Mycorrhizal Fungi in Soil Cadmium Immobilization

Xin Fang,
Xinqing Lee,
Gratien Twagirayezu
et al.

Abstract: Cadmium-contaminated soil significantly threatens global food security and human health. This scenario gives rise to significant worries regarding widespread environmental pollution. Biochar and arbuscular mycorrhizal fungi (AMF) can effectively immobilize cadmium in the soil in an environmentally friendly way. Existing studies have separately focused on the feasibility of each in remediating polluted soil. However, their association during the remediation of cadmium-polluted soils remains unclear. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Research has shown that the inoculation of AM fungi can form a symbiotic relationship with citrus, improving the water and nutrient supply of the host plant citrus through hyphal development [ 4 ]. AM fungi are specialized symbiotic fungi that form symbiosis with most land plants [ 5 , 6 ]. They demonstrate a favorable impact on the soil structure [ 7 ], nutrient uptake and host plants growth [ 8 , 9 ] and alleviate biotic and abiotic stresses on host plants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the inoculation of AM fungi can form a symbiotic relationship with citrus, improving the water and nutrient supply of the host plant citrus through hyphal development [ 4 ]. AM fungi are specialized symbiotic fungi that form symbiosis with most land plants [ 5 , 6 ]. They demonstrate a favorable impact on the soil structure [ 7 ], nutrient uptake and host plants growth [ 8 , 9 ] and alleviate biotic and abiotic stresses on host plants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%